APPLICATION OF BED THICKNESS DISTRIBUTIONS IN LATE EOCENE-OLIGOCENE TURBIDITE DEPOSITS OF GREECE: SOME PRELIMINARY RESULTS - Pantopoulos, G.; Konstantopoulos, P.; Maravelis, A.; Zelilidis, A. (Bulletin of the Geological Society of Greece, 2007)
A simple application of bed thickness distributions was attempted in outcrops of Late Eocene-Oligocene turbidites in three dispersed localities of Greece. The three studied sections are located at Evinohori area (West Greece), Karpathos Island (SE Greece) and Limnos Island (NE Greece). All outcrops show similar sedimentological characteristics. Three types of plots were used: log-log, log-probability and frequency curves. Bed thickness data indicate similarity between West-SE Greece turbidites and discrimination from NE Greece turbidites which is attributed to different basin morphology due to different tectonic processes.